2020
DOI: 10.1038/s41431-020-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of relatives of mucopolysaccharidosis type III patients toward preconception expanded carrier screening

Abstract: Preconception expanded carrier screening (ECS) aims to detect carrier couples of autosomal recessive (AR) disorders before pregnancy in order to increase reproductive autonomy of prospective parents. Genetic knowledge and knowledge gained from experience influence decision making on participation in genetic testing and understanding carrier test results. In this study we assessed whether parents and relatives of patients with the severe AR condition mucopolysaccharidosis type III (MPS III), who are expected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Participants mentioned the benefits of ECS for prospective parents, but also emphasized the benefits from other perspectives (i.e., the future child, family, and society). These positive views are in agreement with the results of earlier survey studies on the attitudes of relatives of MPS III patients (Nijmeijer et al 2020 ) and the general population (Nijmeijer et al 2019 ; Ong et al 2018 ; Plantinga et al 2016 ; Van Steijvoort et al 2020 ). Participants in our study believed that the population needs to be more actively informed about the availability of ECS, which underpins their positive attitudes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Participants mentioned the benefits of ECS for prospective parents, but also emphasized the benefits from other perspectives (i.e., the future child, family, and society). These positive views are in agreement with the results of earlier survey studies on the attitudes of relatives of MPS III patients (Nijmeijer et al 2020 ) and the general population (Nijmeijer et al 2019 ; Ong et al 2018 ; Plantinga et al 2016 ; Van Steijvoort et al 2020 ). Participants in our study believed that the population needs to be more actively informed about the availability of ECS, which underpins their positive attitudes.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in the Netherlands (Nijmeijer et al 2019 ; Plantinga et al 2016 ), Australia (Ong et al 2018 ), and the UK (Briggs et al 2017 ) showed that most prospective parents are willing to pay a maximum of approximately 50–150 euro, whereas the current costs of ECS in many countries worldwide are much higher. In accordance with previous studies (Gilmore et al 2017 ; McClaren et al 2008 ; Nijmeijer et al 2019 ; Nijmeijer et al 2020 ), a lack of perceived personal relevance due to the absence of a genetic disorder in the family was believed to be an important reason for people to refrain from having ECS. Initiatives to inform couples planning a (near) future pregnancy about the rationale of ECS (e.g., aiming at couples without positive family history), for example with public education or awareness campaigns, are essential and were encouraged by all participants in our study.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations